Implications of Malnutrition on Contrast-Associated Acute Kidney Injury in Young and Old Patients Undergoing Percutaneous Coronary Intervention: A Multicenter Prospective Cohort - Liang, Jingjing; Zhang, Lingyu; Huang, Zhidong; He, Yibo; Ling, Yihang; Chen, Kai; Ying, Ming; Lin, Mengfei; Li, Guode; Liu, Jin; Liu, Yong; Liang, Yan; et al. (Frontiers in Nutrition, 2022)
Abstract Background: The relationship between malnutrition and the risk of contrast-associated acute kidney injury (CA-AKI) and the resulting prognosis in patients undergoing percutaneous coronary intervention (PCI) is still not well known. Methods: Patients undergoing PCI were consecutively enrolled in a multicenter study in China (NCT01402232), categorized by nutritional status (non-malnutrition, malnutrition) based on two different cut-off values (i.e., traditional threshold and the best cut-off value based on the ROC curve) for the Controlling Nutritional Status score (CONUT score). The primary endpoint was CA-AKI, diagnosed as a rise of serum creatinine >0.3 mg/dL or >50% than the baseline level occurring within 48 h after the intervention. The secondary endpoint was all-cause mortality. The relationships of malnutrition, CA-AKI, and all-cause mortality were examined using multivariate-adjusted logistic and Cox regression analyses, respectively. Results: Among 2083 patients undergoing PCI (age: 62.8±11.1 years; 79.0% men), 1258 (60.4%) were malnourished. During hospitalization, 80 (3.8%) patients developed CA-AKI events. The incidence of CA-AKI in patients who did not have malnutrition (the non-malnutrition group) and those who did have malnutrition (the malnutrition group) was 1.7% and 5.25%, respectively. Patients with malnutrition had a 2-fold increased adjusted risk of CA-AKI compared to those with no malnutrition (adjusted odds ratio (aOR) [95% confidence interval CI]: 2.41[1.22 to 5.22]). Malnutrition was associated with a 3-fold increased adjusted risk of CA-AKI in patients aged ≤75 years (N=1791, aOR [95% CI]: 3.39[1.46 to 9.25]). Malnourished patients with CA-AKI had a higher risk of all-cause mortality than the others. Similar results were observed in the grouping of supplemental analyses based on the optimal cut-off value of the CONUT score identified by the ROC curve. Conclusions: Malnutrition is strongly associated with an increased risk of CA-AKI in both young and old patients undergoing PCI. Malnourished patients with CA-AKI had a significantly higher risk of all-cause mortality. Further studies are needed to prospectively assess the efficacy of nutritional interventions on outcomes in patients undergoing PCI.